Factors Associated With Severity of COVID-19 Disease in Vaccinated Patients (Journal of Dhaka Medical College, 2024)
Background: Vaccines are considered the most promising approach for restraining the COVID- 19 pandemic. We aimed to identify the disease profile and risk of severe disease despite vaccination. Methods: A cross-sectional study was done from June 2021 to August 2021 in the COVID-19 dedicated hospitals in Dhaka. Total 169 RT-PCR positive adult patients were enrolled by a purposive sampling method who had completed two vaccine doses of COVID-19. Disease profile and severity was identified according to the national guideline of Bangladesh. Results: Of the 169 patients, 19 (11%) had severe diseases. The mean age of the study participants was 50.46 (±14.03) year. The mean age of severely diseased patients was higher than that of non-severe disease 62.63 (±8.27) vs 48.91 (±13.86), p-value